New geographic and altitudinal range extension of the rare Pristimantis divnaeLehr & von May, 2009 (Anura: Craugastoridae) in Peru - Chaparro, Juan C. (2015)
Pristimantis divnae is a nocturnal, semiarboreal species found in lowland forests of southern Peru in the departments of Cusco, Madre de Dios and Puno. Here, we present a 382 km geographical range extension and the first record at 980 m elevation, increasing the known vertical distribution by 678 m. This is also the first record of this species from premontane forest, uggesting that habitat requirements ofP. divnaeare broader than originally anticipated.